2010
DOI: 10.3109/07853890.2010.518156
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and immune response in acute aortic dissection

Abstract: Our results strongly support the hypothesis of a pivotal role of innate immunity in type-A Stanford AAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
125
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 35 publications
11
125
1
Order By: Relevance
“…Two risk models including preoperative and intraoperative variables have been developed by the International Registry of Acute Aortic Dissection and are generally used, but in recent studies several biochemical markers of vascular injury, thrombosis, and inflammation have been evaluated as contributors in the diagnosis of acute aortic dissection or as risk prediction tools. These studies suggest that AAD is associated with both tissue-level and systemic inflammatory reaction, and one of the inflammatory markers, C-reactive protein (CRP), is a useful marker to predict in-hospital and long-term adverse events (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Two risk models including preoperative and intraoperative variables have been developed by the International Registry of Acute Aortic Dissection and are generally used, but in recent studies several biochemical markers of vascular injury, thrombosis, and inflammation have been evaluated as contributors in the diagnosis of acute aortic dissection or as risk prediction tools. These studies suggest that AAD is associated with both tissue-level and systemic inflammatory reaction, and one of the inflammatory markers, C-reactive protein (CRP), is a useful marker to predict in-hospital and long-term adverse events (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…This condition may determine the reduction of perfusion of numerous organs with devastating complications (1-3). Recent evidence suggests inflammation as the principal mechanism of aorta AD medial degeneration (6,(9)(10)(11)(12). In particular, it has been demonstrated that inflammatory cells, such as lymphocytes and macrophages, not only increase the expression of proteases and cell adhesion molecules, but also release reactive oxygen species.…”
mentioning
confidence: 99%
“…In particular, it has been demonstrated that inflammatory cells, such as lymphocytes and macrophages, not only increase the expression of proteases and cell adhesion molecules, but also release reactive oxygen species. Thus, they contribute to the apoptosis of vascular smooth muscle cells (VSMCs) in the aortic artery, and finally lead to medial degradation (6,(9)(10)(11)(12). Furthermore, this condition determines increases in systemic inflammatory molecules [i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phase is mediated as well by tumor necrosis factor-alpha, interleukin (IL)-6, IL-8 and macrophage metalloprotease-12, which participate in tissue breakdown and augment the local inflammation. [13][14][15] On the other hand, areas of chronic response with appearance of granulation tissue, new capillaries and collagen deposition are building up in the outer layers of media. This type of reaction can be demonstrated only days or weeks after the initial assault, and its biological significance may consist of the separation of the damaged area and strengthening of the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%